1999
DOI: 10.1159/000022521
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Circulating 17β-Oestradiol with Haemostatic Factors in Healthy Postmenopausal Women

Abstract: The aim of the study was to evaluate any correlation between the circulating oestrogenic hormone 17β-oestradiol and haemostatic factors in healthy postmenopausal women. In keeping with this objective, the correlations were evaluated irrespective of whether the source of the hormone was purely endogenous or exogenous as well. Accordingly, a univariate correlation adjusted for age, body mass index, and duration of menopause was determined in 42 healthy postmenopausal women aged 47–78 years, 19 of whom were self-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…Genome-wide screens demonstrate the existence of high-affinity estrogen receptor-binding sites in mouse liver for α 2 -AP gene [30,31]. Our present data that plasma α 2 -AP levels were significantly elevated in mice with OVX, compared to control mice, were compatible with those previous data [28,29]. Moreover, estrogen suppressed the expression of α 2 -AP in mouse hepatocytes.…”
Section: Role Of Erk1/2 and P38 Mapk In α 2 -Ap Activitysupporting
confidence: 92%
See 1 more Smart Citation
“…Genome-wide screens demonstrate the existence of high-affinity estrogen receptor-binding sites in mouse liver for α 2 -AP gene [30,31]. Our present data that plasma α 2 -AP levels were significantly elevated in mice with OVX, compared to control mice, were compatible with those previous data [28,29]. Moreover, estrogen suppressed the expression of α 2 -AP in mouse hepatocytes.…”
Section: Role Of Erk1/2 and P38 Mapk In α 2 -Ap Activitysupporting
confidence: 92%
“…Based on these results, we speculate that circulating α 2 -AP is produced in the liver and kidney, but is not locally produced in the bone. Cleuren et al reported that administration of estrogen significantly reduced plasma α 2 -AP in mice [28] and Mukherjee et al found a negative correlation between blood α 2 -AP and estradiol levels in patients undergoing hormone replacement therapy [29]. Genome-wide screens demonstrate the existence of high-affinity estrogen receptor-binding sites in mouse liver for α 2 -AP gene [30,31].…”
Section: Role Of Erk1/2 and P38 Mapk In α 2 -Ap Activitymentioning
confidence: 99%
“…It is known that during aging the number of neurons is reduced and the protein synthesis and turnover rate is decreased (Zs-Nagy 1985). Mukherjee et al (1999) who showed that the total protein synthesis is significantly higher in adult males than females and decreases in old males but not in females, also reported that estradiol treatment enhances the synthesis of proteins remarkably in both sexes, 9.7-fold in adults, 4.1-fold in old males, 4.0-fold in adults and 3.4-fold in old females. On the other hand, the intracellular dry mass content increases i.e.…”
Section: Discussionmentioning
confidence: 96%
“…The effect of HRT on coagulation factors is also a matter of controversy. An inverse correlation between estradiol and antithrombin III levels has been observed in healthy postmenopausal women pooled without distinction between HRT users and nonusers (Mukherjee et al, 1999). Controlled prospective studies have suggested that HRT is associated with decreased levels of coagulation inhibitors, although a net activation of coagulation is not observed (Hoibraaten et al, 2000;van Baal et al, 2000).…”
Section: Discussionmentioning
confidence: 99%